Ekonomista z Wilna - dorobek naukowy Władysława Mariana Zawadzkiego - Klimiuk, Zbigniew (Przegląd Wschodnioeuropejski, 2017)
Wladysław Marian Zawadzki (1885–1939), was born in Vilno, Polish economist, Minister of Treasure (1932–1935), pioneered mathematical economics in Poland (the Walrasian mathematical economist). The conservative professor of economics at the School of Commerce (SGH) in Warsaw and the Stefan Batory University of Wilno (1919–1931). The SGH had at this time the stronger team of theoreticians. It was led by Wladyslaw Zawadzki. He was a very thorough exposition of J.M. Keynes’s monetary analisis, contrasting it with his earlier ideas in the Treatise on Money and the Tract on Monetary Reform. Zawadzki regretted Keynes’s etatism but comforted himself and his readers that Keynes had changed his mind at least twice before The General Theory.